2020
DOI: 10.21203/rs.3.rs-22466/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors for the development of preoperative oxygenation impairment in acute aortic dissection in hypertensive patients

Abstract: Background Acute aortic dissection (AAD) is an acute life-threatening cardiovascular disease, which is frequently complicated with oxygenation impairment (OI). We aim to investigate predictors of the development of OI in the patients with AAD.Methods We retrospectively collected clinical data of AAD in hypertensive patients from July 2012 to March 2020. The patients included in this study were divided into OI (+) group (oxygenation index≤200) and OI (-) group (oxygenation index>200). Both groups were compar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Many studies have shown that SA is likely protection factors to be the type A AAD, type A AAD occurs, a large number of inflammatory cytokines release, increase SA decomposition, led to lower SA, blood vessels in the colloid osmotic pressure drop, cause oedema after large amounts of fluid leakage, causing the blood volume is reduced, viscera perfusion decreased, AKI, pulmonary edema, cerebral edema and other serious complications can further affect the postoperative outcome of patients with Type A AAD. Low SA reduces the ability of scavenging oxygen-free radicals and inhibiting inflammatory response, and endothelial cells are damaged, and the elasticity of aortic vascular wall decreases, ultimately affecting the outcome of Type A AAD [Keskin 2021;Gao 2019;Zhao 2020;Weiner 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that SA is likely protection factors to be the type A AAD, type A AAD occurs, a large number of inflammatory cytokines release, increase SA decomposition, led to lower SA, blood vessels in the colloid osmotic pressure drop, cause oedema after large amounts of fluid leakage, causing the blood volume is reduced, viscera perfusion decreased, AKI, pulmonary edema, cerebral edema and other serious complications can further affect the postoperative outcome of patients with Type A AAD. Low SA reduces the ability of scavenging oxygen-free radicals and inhibiting inflammatory response, and endothelial cells are damaged, and the elasticity of aortic vascular wall decreases, ultimately affecting the outcome of Type A AAD [Keskin 2021;Gao 2019;Zhao 2020;Weiner 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Low SA reduces the ability of scavenging oxygen free radicals and inhibiting in ammatory response, and endothelial cells are damaged, and the elasticity of aortic vascular wall decreases. Ultimately affecting the outcome of Type A AAD [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, TNFα, and CRP are common pro-inflammatory cytokines that have been reported as overexpressed in patients with aortic dissection (3)(4)(5)(6)(7)(8)(9)(10). Studies found that inflammatory cytokines, including CRP, IL-6, and IL-8, might be associated with the development of acute lung injury in patients with acute TAAD (5,14,(18)(19)(20)(21), and WBC levels could be elevated in these patients (5,18). In this study, we found that various inflammatory response indicators, including WBC parameters and inflammatory cytokines, were activated in patients with TAAD and significantly higher than in those in patients with ARA.…”
Section: Discussionmentioning
confidence: 99%